GE_GERICHTE P/8042/2007 vom 5. Dezember 2007 - GE Cour de justice (2007)
DROIT D'ÊTRE ENTENDU; GARANTIE DE PROCÉDURE; DIFFAMATION; AUTODÉFENSE | CPP.10; CPP.134; CPP.185; CPP.194; CP.14; CP.173; CP.174; CP.163; CP.303